Gastrópodos terrestres de la región oriental de San Luis Potosí, México - Correa-Sandoval, Alfonso; García Cubas Gutiérrez, Antonio; Reguero Reza, María Martha (Instituto de Ecología, A.C., 1998)
Forty five genera, 87 species and 9 subspecies of terrestrial gastropods belonging to 24 familias are recordad for the eastern región of the State of San Luis F'otosí. Forty two species are new records. The famiiy with more species (17) is Spiraxidae, The species with greater distribution by localities are Practicolella berlandieriana, Thysanophora horni and Cecilioides consobrina veracruzensis.